2014
DOI: 10.1111/ipd.12132
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical control of biofilm in children with cerebral palsy: a randomized clinical trial

Abstract: All methods reduced biofilm. Effectiveness was similar between manual brushing and with the electric toothbrush on, whereas both these methods achieved better results in comparison with the electric toothbrush switched off.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 21 publications
1
20
0
1
Order By: Relevance
“…Seven studies evaluated mechanical intervention (Table ): conventional manual toothbrush with versus without Internet‐based oral hygiene education (Popple et al, ); conventional manual toothbrushes versus modified toothbrushes—triple‐headed toothbrush (Doǧan, Alaçam, Aşici, Odabaş, & Seydaoǧlu, ), handle‐modified toothbrush (Crawford, Burril, & Grogan, ), individually modified toothbrush (Damle & Bhavsar, ); powered toothbrushes versus conventional manual toothbrushes (Doǧan et al, ; Ferraz et al, ; Gertenrich & Lewis, ; Shaw, Harris, Maclaurin, & Foster, ), or versus triple‐headed toothbrush (Doǧan et al, ). Studies differed in assessment methods of dental plaque outcome, and the most common index was Silness & Löe Plaque Index.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies evaluated mechanical intervention (Table ): conventional manual toothbrush with versus without Internet‐based oral hygiene education (Popple et al, ); conventional manual toothbrushes versus modified toothbrushes—triple‐headed toothbrush (Doǧan, Alaçam, Aşici, Odabaş, & Seydaoǧlu, ), handle‐modified toothbrush (Crawford, Burril, & Grogan, ), individually modified toothbrush (Damle & Bhavsar, ); powered toothbrushes versus conventional manual toothbrushes (Doǧan et al, ; Ferraz et al, ; Gertenrich & Lewis, ; Shaw, Harris, Maclaurin, & Foster, ), or versus triple‐headed toothbrush (Doǧan et al, ). Studies differed in assessment methods of dental plaque outcome, and the most common index was Silness & Löe Plaque Index.…”
Section: Resultsmentioning
confidence: 99%
“…When switched off, the toothbrushes had to be used manually. One study reported that powered toothbrush switched on was more effective than switched off (Ferraz et al, ). In the five comparisons of powered toothbrushes versus manual toothbrushes (conventional and triple‐headed), powered toothbrushes were deemed more effective than the manual toothbrushes in two of the five comparisons (one study; Doǧan et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Além disso, proporcionam bolsas periodontias mais rasas e removem o biofilme dentário mais eficientemente que a escovação manual (Heanue et al, 2003;Deacon et al, 2010;Hovliaras et al, 2015;Re et al, 2015;Ikeda et al, 2016;Kurtz et al, 2016;Davidovich et al, 2017;de Jager et al, 2017;Erbe et al, 2018;Kaizer et al, 2018). A eficácia do uso de escovas dentais para melhora significativa da higiene bucal foi comprovada por Nikolaev et al, (2016) e Ferraz et al, (2015). Entretanto podem ocasionar danos clinicamente relevantes aos tecidos mineralizados e tecidos moles (Boyd, 1997;Boyd et al, 1997;He et al, 2001;Robinson, 2011;Van der Weijden et al, 2011.;Fukumoto et al, 2014;Graetz et al, 2017).…”
Section: Introductionunclassified